PENGETAHUAN IBU MENYUSUI TENTANG PIJAT LAKTASI DI BPM SYAFLINA FITRI KABUPATEN ROKAN HULU - Andria; Wulandari, Sri; Yesti, Herma; Kristina, Evi; Hasibuan, Darma Afni (Fakultas Ilmu Kesehatan, 2025)
Breast milk is the best source of nutrition for term and preterm babies during the first six months of life. Exclusive breastfeeding for the first six months is recommended, followed by the addition of solid foods after six months of age. Unfortunately, there are several obstacles to breastfeeding, one of which is that breast milk does not flow smoothly. Breastfeeding mothers will feel stressed when their babies want to breastfeed but the flow of breast milk is blocked. Based on UNICEF and WHO data through the 2021 Global Breastfeeding Scorecard data, the level of breastfeeding remains lower than needed. to protect the health of mothers and children. In 2013-2018, 48% of newborns started breastfeeding within one hour of birth. Although this program has been running, there are still some mothers who have difficulty breastfeeding on the grounds that breast milk is not flowing smoothly. The purpose of the study was to determine the knowledge of breastfeeding mothers about lactation massage. This research method is descriptive. The population in this study was 77 respondents. The results of the study showed that mothers with less knowledge were 32 people (41.6%), mothers with sufficient knowledge were 16 people (20.8%) and mothers with good knowledge were 29 people (37.7%). The conclusion from the results of the study, there are still many postpartum mothers who do not understand about lactation massage, both its benefits and massage procedures. So it is hoped that after this study ends, every breastfeeding mother should better understand the benefits of lactation massage so that the problem of breast milk not flowing smoothly can be immediately resolved.